A comprehensive analysis of variability in the sulci that define the inferior frontal gyrus in the chimpanzee (Pan troglodytes) brain. Issue 1 (20th July 2022) - Hopkins, William D.; Sprung‐Much, Trisanna; Amiez, Celine; Procyk, Emmanuel; Petrides, Michael; Schapiro, Steven J.; Sherwood, Chet C.
Abstract: Objectives: In the human brain, the inferior frontal gyrus (IFG) is comprised of three morphological regions, which include the pars opercularis, pars triangularis, and pars orbitalis. These brains regions are implicated in a number of cognitive and linguistic functions, and the pars opercularis and pars triangularis of the language dominant hemisphere are collectively referred to as Broca's area. Evolution of the morphology of the IFG has been a topic of study in comparative neuroscience. Materials and Methods: Using magnetic resonance images (MRI) from 294 chimpanzees with known pedigrees, we quantified the folding patterns, surface area, and depth of three sulci and their subdivisions that define the IFG. Results: Chimpanzees show considerable individual variation in IFG sulci. A higher proportion of males and chimpanzees with better orofacial motor control had a bifurcation in the dorsal limb of the fronto‐orbital sulcus. For surface area and depth, chimpanzees with better orofacial motor control had greater leftward asymmetries in surface area and increased gyrification for the fronto‐orbital sulcus and greater rightward biases for the inferior precentral sulcus. Quantitative genetic analyses revealed that the average surface area and depth for three of the five sulci subdivisions were significantly heritable. By contrast, we found no evidence for heritability in asymmetries for any of the sulci. Discussion: These findings provide context to understanding evolutionary selection for increasing motor, cognitive and linguistic functions among primates, and contribute an essential comparative framework for interpreting IFG evolution in the human lineage.